The amalgamation of eastern and western philosophies within Idokan Karate - Cynarski, Wojciech Jan; Johnson, John Arthur (Revista de Artes Marciales Asiáticas, 2023)
Every school of the Japanese martial art of karate possesses special values and norms unique to its practice. Unsurprisingly, the philosophy of Idokan karate is therefore similar to other schools while remaining distinct in the myriad of martial art practices. Idokan karate possesses a practical philosophy (i.e., applicable to everyday life) influenced by Eastern and Western belief systems that are internalized and utilized by its practitioners as forms of today’s civilian warrior path. This single case study examines the prominent Idokan ethics, values, and rules as well as details its specific and symbolic content. It makes use of the hermeneutic phenomenology research method to present a content analysis of literature on Idokan within the wider discourse of martial arts studies. A broad discourse analysis of these topics in both scientific studies and popular publications was conducted. In doing so, this study’s practical implications are that it not only provides a glimpse into the uniqueness of Idokan karate philosophy but also into that of the vastness of the great martial arts menagerie. Idokan karate philosophy is derived distinctively from its founders’ understandings of Chinese and Japanese martial arts, Taoism, and Christianity and dictates practitioners a unique morality. Such teleology comes from special values, rules, and aims embedded in Idokan teachings. In normative ethics, the Decalogue and nobility of spirit (the Homo Creator Nobilis) are most important. Tao in Idokan is understood as God’s Word, the principle of love, and the way of (Christian) heaven.